Przemoc w konsekwencjach pandemii COVID-19: analiza społeczno-kulturowa - Gruchoła, Małgorzata ca. 20./21. Jh. (Roczniki kulturoznawcze, 2022)
At a time of crisis, which may be caused by a natural disaster (e.g. the COVID-19 pandemic), each social group looks for a ‘scapegoat’ (René Girard's theory). This mechanism is illustrated in the article by the number of deaths due to SARS-CoV-2 treated as a collective victim. The aim of the article was a study of the sources and forms of violence and to identify a scapegoat in the perception of the COVID-19 pandemic based on 24 research of the Eurobarometer: Public opinion monitoring in the time of COVID-19, covering the period from the 20th of March 2020 to the 30th of June 2021. The respondents' opinions on the consequences of a pandemic treated as a manifestation of violence were analyzed in three areas: economic, social and health. Applied were a quantitative analysis of the content of reports, a qualitative analysis of the contents, comparative and analytical descriptive methods. Six detailed research hypotheses were adopted, 3 of which were confirmed. The main hypothesis was also confirmed, but only for the first surge assuming that the number of deaths in individual EU countries, recorded in subsequent waves of the COVID-19 pandemic, treated as a collective victim, is proportional to the total number of recorded cases of economic, social and health violence in a given country. The increase in deaths implies an increase in the identified violent acts.